2007
DOI: 10.1038/sj.ejcn.1602779
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of low bone mineral density in the elderly: the role of dietary intake, nutritional status and sarcopenia

Abstract: Objectives: The aims of this study were to investigate the relationship between sarcopenia, dietary intake, nutritional indices and hip bone mineral density (BMD) in the elderly, and to estimate the risk of low BMD due to specific independent predictor thresholds. Subjects and methods: Body mass index (BMI), serum albumin, energy and protein intake were studied in 352 elderly outpatients (216 women aged 73.575.3 years and 136 men aged 73.975.6 years). BMD at different hip sites and appendicular skeletal muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
3
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 33 publications
4
68
3
11
Order By: Relevance
“…However, studies have shown contradicting associations, in relation to presarcopenia and sarcopenia, with BMD and diagnosis of osteoporosis (17,18). Coin and cols., after evaluation of 136 men (mean age 73 years), found no significant association between BMD of the femoral neck and total hip with RASM < 7.26 kg/m², that is, diagnosed with pre-sarcopenia according to the EWGSOP (8,19). More recently, Verschueren and cols.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown contradicting associations, in relation to presarcopenia and sarcopenia, with BMD and diagnosis of osteoporosis (17,18). Coin and cols., after evaluation of 136 men (mean age 73 years), found no significant association between BMD of the femoral neck and total hip with RASM < 7.26 kg/m², that is, diagnosed with pre-sarcopenia according to the EWGSOP (8,19). More recently, Verschueren and cols.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include inflammatory factors since the age-related increase in pro-inflammatory cytokines is associated with sarcopenia (Schaap et al, 2006) and bone resorption (Lauretani et al, 2006) in older men. Nutritional factors, other than those measured herein, such as protein intake, or the intake of fatty acids for example, might also be involved in the relationship between RASM and FN BMD in adult men (Coin et al, 2008). …”
mentioning
confidence: 99%
“…La hipoalbuminemia es buen ejemplo, con valores en la presente muestra que concuerdan con la literatura 29,30 . Otro lo constituyen fármacos indicados para tratar enfermedades frecuentes en el mayor, pero que son osteolesivos 31,32 .…”
Section: Discussionunclassified